AGAINST SPANKING. Issue 62 (2022) - Simpson, James
Abstract : In a recent article in this journal ( THINK 54), Timothy Hsiao argues that spanking a misbehaving child is morally permissible on the grounds that it's what the child deserves. However, in this short article, I argue that Hsiao's argument in this connection is either obviously unsound or invalid.